Some issues of registration and reproduction of information touching upon objects of material and spiritual culture using technologies of the state insurance documentation fund of Ukraine. - Babenko, V. V.; Nadtochiy, I. I.; Savich, A. V.; Timrov, O. O. (Інститут проблем реєстрації інформації НАН України, 2019)
A methodology of creating images in digital form, containing information about cultural values, for the formation, management and use of the insurance fund of documentation (IFD) of Ukraine on the basis of the creation and registration of their information meanings (complex digital images) is presented. Under the information content of the material results of human creation is understood the result of the allocation of human context of knowledge about them, which should be understood as an organized, integrated collection of facts and generalizations.Solving the problem of storing the informational content of the material results of human creation is the complex solution of the following tasks: 1) allocation of human context of knowledge about the material results of human creation, that is, the creation of a very specific information; 2) presentation of this information to data; 3) determination of the type of data representation and the medium corresponding to such representation.For this purpose, a method of creating images in digital form containing information about cultural values is proposed, the essence of which is to reduce such actions into a single technological process: conducting scientific attribution and determining the attributes to be visualized and their digitization; production and storage of microfilms IFD with information about cultural values; restoring information about cultural values from IFD microfilms specified quality.